Phytochemistry, pharmacology and toxicology of Peganum harmala (Bangladesh Journal of Pharmacology, 2022)
This systematic review focuses on the phytochemical, pharmacological and toxicological aspects of P. harmala, which aims to construct the scientific foundations of P. harmala-based drugs. Until now, over 390 secondary metabolites, including alkaloids, flavonoids, triterpenoids, phenolic acids, anthraquinones, fatty acids, and essential oils, had been identified from different parts of P. harmala. The plant and its important bioactive compounds demonstrated various pharmacological activities, mainly including antimicrobes, anti-cancer, anti-atherogenesis, anti-diabetes, anti-inflammation, neuropsychological, analgesic, hepatoprotective, bronchodilating, gastroprotective, diuretic, and hypothermic effects. However, excessive use of high doses of P. harmala extract could lead to serious hepatic, nephritic, and neuropathic toxicities. Current evidence validates the claimed effectiveness of traditional uses of P. harmala for many symptoms.